Hollow particles, method for producing the hollow particles, resin composition, and resin molded body and laminate using the resin composition

JP7633328B2Active Publication Date: 2025-02-19SETOLAS HLDG INC
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
JP2023129337
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-08-08
Publication Date
2025-02-19
Estimated Expiration
2041-05-07

AI Technical Summary

Benefits of technology

【0010】 本発明の実施形態によれば、一次粒子の粒子サイズが所定の均一性を満足する中空粒子を用いることで、誘電特性を向上させ得る。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007633328000003
    Figure 0007633328000003
  • Figure 0007633328000004
    Figure 0007633328000004
  • Figure 0007633328000005
    Figure 0007633328000005
Patent Text Reader

Abstract

To provide hollow particles that are capable of improving dielectric properties.SOLUTION: Hollow particles according to an embodiment of the present invention contain silica in which primary particles satisfy DSL of the following formula (1), and fracture strength is 10 MPa or higher: 1≤DSL≤1.5...(1) where DSL=D75L / D25L, and D25L and D75L are the 25th and 75th values, respectively, obtained by measuring the long diameter of 100 randomly selected primary particles in a scanning electron microscope observation and arranging them from the smallest to the largest.SELECTED DRAWING: Figure 4A
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to hollow particles, a method for producing the hollow particles, a resin composition, and a resin molded article and a laminate using the resin composition. [Background technology]

[0002] For example, in the field of information and communication devices, there is a demand for low dielectric constants and low dielectric loss tangents for electronic components (typically resin components) to accommodate communication in high frequency bands. To achieve this, for example, it has been proposed to include air with a low relative dielectric constant in the components. Specifically, it has been proposed to introduce air using hollow particles (for example, see Patent Document 1).

[0003] The recent trend toward higher speeds and larger capacities in information and communication devices has created demands for further improvements in dielectric properties. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2007-56158 A Summary of the Invention [Problem to be solved by the invention]

[0005] The present invention has been made to solve the above problems, and one of its objects is to improve dielectric properties. [Means for solving the problem]

[0006] The hollow particles according to the embodiment of the present invention comprise silica and have a primary particle D SL satisfies the following formula (1) and has a breaking strength of 10 MPa or more. 1≦D SL ≦1.5 (1) Here, D SL =D 75L / D 25L and D 25Land D. 75L The major axis diameters of 100 randomly selected primary particles were measured using a scanning electron microscope, and the 25th and 75th largest values ​​were measured when the particles were arranged in order of size from smallest to largest. In one embodiment, the hollow particles have a BET specific surface area of ​​30 m 2 / g or less. In one embodiment, the hollow particles have an integrated pore volume of pores having a diameter of 1 nm to 100 nm of 0.1 cc / g or less. In one embodiment, the hollow particles have a hollow ratio of 30% or more and 95% or less. In one embodiment, the hollow particles have an aspect ratio of less than 2. In one embodiment, the hollow particles have a major axis of 0.5 μm or more and 10 μm or less. In one embodiment, the hollow particles have a shell thickness of 25 nm or more and 500 nm or less. In one embodiment, the silica is amorphous silica. In one embodiment, the hollow particles contain Al, and the molar ratio of Al / Si is 0.0001 or more and 0.1 or less. In one embodiment, the hollow particles contain Na, and have a molar ratio of Na / Si of 0.001 or more and 0.025 or less.

[0007] A resin composition according to another embodiment of the present invention includes a resin and the hollow particles described above.

[0008] A resin molded product according to yet another embodiment of the present invention is formed from the above-mentioned resin composition. A laminate according to yet another embodiment of the present invention has a resin layer formed from the above-mentioned resin composition. In one embodiment, the resin layer has a thickness of 25 μm or less.

[0009] According to yet another embodiment of the present invention, a method for producing the hollow particles includes coating a core particle with a shell-forming material to obtain a core-shell particle, removing the core particle from the core-shell particle to obtain a hollow particle precursor, and coating the hollow particle precursor with a shell-forming material. In one embodiment, the core particle contains an alunite type compound represented by the following general formula (I). M a [Al 1-x M' x ]3(SO4 2- ) y (OH) z mH2O (I) In formula (I), M is Na + , K + , NH4 + and H3O + M' is at least one cation selected from the group consisting of Cu 2+ , Zn 2+ , Ni 2+ , Sn 4+ , Zr 4+ and Ti 4+ and wherein a, m, x, y and z satisfy 0.8≦a≦1.35, 0≦m≦5, 0≦x≦0.4, 1.7≦y≦2.5, and 4≦z≦7, respectively. In one embodiment, the method includes calcining the core-shell particles before removing the core particles. The core-shell particles may be calcined at 650° C. or less. In one embodiment, the method includes calcining the hollow particle precursor coated with the shell-forming material. The hollow particle precursor may be calcined at 900° C. or higher. In one embodiment, the production method includes subjecting the hollow particle precursor to an acid treatment before calcining the hollow particle precursor. In one embodiment, the shell-forming material comprises sodium silicate. Effect of the Invention

[0010] According to an embodiment of the present invention, the dielectric properties can be improved by using hollow particles in which the particle size of the primary particles satisfies a predetermined uniformity. [Brief description of the drawings]

[0011] [Figure 1] FIG. 2 is a schematic diagram illustrating a major axis and a minor axis. [Diagram 2] 1 is a schematic cross-sectional view of a laminate in one embodiment of the present invention. [Figure 3A] 1 is a SEM photograph of hollow particles of Example 1. [Figure 3B] 1 is a SEM photograph of hollow particles of Example 2. [Figure 3C] 1 is a SEM photograph of hollow particles of Comparative Example 1. [Figure 4A] 1 is a TEM observation photograph of hollow particles of Example 1. [Figure 4B] 1 is a TEM observation photograph of hollow particles of Example 2. [Figure 4C] 1 is a TEM observation photograph of hollow particles of Comparative Example 1. [Figure 5A] 2 is a SEM photograph of a cross section of the resin molded product of Example 1. [Figure 5B] 1 is a SEM photograph of a cross section of a resin molded body of Example 2. [Figure 5C] 1 is a SEM photograph of a cross section of a resin molded body of Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to these embodiments.

[0013] (Definition of terms) The definitions of terms used in this specification are as follows. 1. Major axis of particle This is a value measured by a scanning electron microscope (SEM) and is the average value of the long diameter (e.g., L in Figure 1) of randomly selected primary particles. Note that primary particles are the smallest particles observed by SEM and are distinguished from aggregated particles (secondary particles). 2. Minor diameter of particle This value is measured by SEM observation and is the average value of the minor axis (for example, T in Figure 1) of randomly selected primary particles. 3. Aspect ratio (long diameter / short diameter) This value is calculated by subtracting the minor axis of the particle from the major axis of the particle.

[0014] A. Hollow particles The hollow particles in one embodiment of the present invention are typically formed of silica (e.g., amorphous silica). The silica content of the hollow particles is, for example, 95% by weight or more, preferably 97% by weight or more, and more preferably 98% by weight or more.

[0015] The hollow particles may contain Al. The Al content is, for example, 0.1 or less in terms of Al / Si molar ratio, preferably 0.08 or less, and more preferably 0.04 or less. On the other hand, the Al content is, for example, 0.0001 or more in terms of Al / Si molar ratio. The Al content may be, for example, 0.001 or more in terms of Al / Si molar ratio. The Al / Si molar ratio can be determined by composition analysis using energy dispersive X-ray spectroscopy (EDS).

[0016] The hollow particles may contain Na. The Na content is, for example, 0.025 or less, preferably 0.020 or less, in terms of the Na / Si molar ratio. On the other hand, the Na content is, for example, 0.001 or more, in terms of the Na / Si molar ratio. The Na / Si molar ratio can be determined by composition analysis using energy dispersive X-ray spectroscopy (EDS).

[0017] The Kubelka-Munk conversion (hereinafter sometimes referred to as KM conversion) silanol group area of ​​the hollow particles is preferably 1500- / g or less, more preferably 1000- / g or less, and even more preferably 700- / g or less. According to an embodiment of the present invention, it is possible to achieve both a high hollow ratio and / or high breaking strength described below and such a low KM conversion silanol group area. On the other hand, the KM conversion silanol group area of ​​the hollow particles is, for example, 1- / g or more.

[0018] The primary particle size of the hollow particle is 1≦D SL ≦1.5, preferably 1≦D SL ≦1.4, and more preferably 1≦D SL ≦1.3, where D SL D 75L / D 25L and D 25L and D. 75L The major axis diameters of 100 randomly selected primary particles were measured using a scanning electron microscope, and the 25th and 75th largest values ​​were measured when the particles were arranged in order of size from smallest to largest.

[0019] The primary particle size of the hollow particle is 1≦D ST It is preferable that 1≦D ST ≦1.4, and more preferably 1≦D ST ≦1.3, where D ST D 75T / D 25T and D 25T and D. 75T The minor axis diameters of 100 randomly selected primary particles were measured using a scanning electron microscope, and the 25th and 75th smallest sizes were measured when the particles were arranged in order of size.

[0020] The aspect ratio of the hollow particles is preferably less than 2, and more preferably not more than 1.9. On the other hand, the aspect ratio of the hollow particles is 1 or more, and preferably exceeds 1, and more preferably is 1.1 or more.

[0021] The shape of the hollow particles may be any appropriate shape. Examples of the shape of the hollow particles include ellipsoid, sphere, aggregate, scale, plate, membrane, cylinder, prism, flat, go stone, and rice grain. Preferably, the sphere and go stone shapes are used. By using such shapes, for example, the above-mentioned D SL and D. ST can be satisfactorily satisfied.

[0022] The major axis of the hollow particles is preferably 0.5 μm or more, and more preferably 1 μm or more. For example, this is because the hollow ratio described below can be fully satisfied. On the other hand, the major axis of the hollow particles is preferably 10 μm or less, and more preferably 5 μm or less. For example, this is because it can greatly contribute to the miniaturization (thinning) of the members in which they are used.

[0023] The minor axis of the hollow particles is preferably 0.25 μm or more, and more preferably 0.5 μm or more. For example, this is because the hollow ratio described below can be fully satisfied. On the other hand, the minor axis of the hollow particles is preferably 10 μm or less, and more preferably 5 μm or less. For example, this is because it can greatly contribute to the miniaturization (thinning) of the members in which they are used.

[0024] The thickness of the shell of the hollow particles is preferably 25 nm or more, more preferably 50 nm or more, and even more preferably 75 nm or more. With such a thickness, for example, when preparing a resin composition described later, the hollow particles can be effectively prevented from being broken. On the other hand, the thickness of the shell of the hollow particles is preferably 500 nm or less, more preferably 350 nm or less, and even more preferably 250 nm or less. With such a thickness, the hollow ratio described later can be fully satisfied, and it can greatly contribute to improving the dielectric properties and reducing the weight. The shell thickness can be measured by TEM observation. For example, it can be obtained by measuring the shell thickness of randomly selected hollow particles and calculating the average value.

[0025] The hollow ratio of the hollow particles is preferably 30% or more, more preferably 40% or more, even more preferably 45% or more, and particularly preferably 50% or more. Such a hollow ratio can, for example, greatly contribute to improving dielectric properties and reducing weight. On the other hand, the hollow ratio of the hollow particles is preferably 95% or less, more preferably 90% or less, even more preferably 85% or less, and particularly preferably 80% or less. Such a hollow ratio can effectively prevent the hollow particles from breaking, for example, when preparing the resin composition described below. The hollow ratio can be calculated from the major axis and minor axis and the thickness of the shell.

[0026] The ratio of the shell thickness to the major axis (shell thickness / major axis) is preferably 0.01 or more and 0.33 or less, more preferably 0.02 or more and 0.25 or less, and even more preferably 0.03 or more and 0.25 or less.

[0027] The BET specific surface area of ​​the hollow particles is preferably 30 m 2 / g or less, and more preferably 20m 2 / g or less, more preferably 10m 2 On the other hand, the BET specific surface area of ​​hollow particles is, for example, 0.5 m 2 / g or more, and 1m 2 / g or more.

[0028] The pore volume of the hollow particles (cumulative pore volume of pores with a diameter of 1 nm to 100 nm) is preferably 0.1 cc / g or less, more preferably 0.08 cc / g or less, and even more preferably 0.06 cc / g or less. Such a pore volume can effectively prevent the resin from penetrating into the hollow particles in the resin composition described below, and can greatly contribute to improving the dielectric properties. On the other hand, the pore volume of the hollow particles (cumulative pore volume of pores with a diameter of 1 nm to 100 nm) is, for example, 0.01 cc / g or more.

[0029] The pore volume of the hollow particles (cumulative pore volume of pores with a diameter of 1 nm to 10 nm) is preferably 0.01 cc / g or less, more preferably 0.007 cc / g or less, and even more preferably 0.005 cc / g or less. Such a pore volume can effectively prevent the resin from penetrating into the hollow particles in the resin composition described below, and can greatly contribute to improving the dielectric properties. On the other hand, the pore volume of the hollow particles (cumulative pore volume of pores with a diameter of 1 nm to 10 nm) is, for example, 0.001 cc / g or more.

[0030] The breaking strength of the hollow particles is 10 MPa or more, more preferably 12 MPa or more, even more preferably 14 MPa or more, and particularly preferably 16 MPa or more. With such breaking strength, for example, when preparing a resin composition described later, the hollow particles can be effectively prevented from breaking. As a result, the hollow state of the particles is maintained, which can greatly contribute to improving the dielectric properties. On the other hand, the breaking strength of the hollow particles is, for example, 800 MPa or less.

[0031] In one embodiment, the hollow particles are surface-treated with any suitable surface treatment agent, such as at least one selected from the group consisting of higher fatty acids, anionic surfactants, cationic surfactants, phosphate esters, coupling agents, esters of polyhydric alcohols and fatty acids, acrylic polymers, and silicone treatment agents.

[0032] Any suitable method may be adopted as the method for producing the hollow particles. The method for producing hollow particles according to one embodiment of the present invention includes obtaining core-shell particles by coating a core particle with a shell-forming material, obtaining a hollow particle precursor by removing the core particle from the core-shell particle, and coating the hollow particle precursor with a shell-forming material. By coating the hollow particle precursor with a shell-forming material, for example, a strong shell can be formed while suppressing a decrease in hollow ratio. Specifically, the hollow particle precursor (shell) obtained by removing the core particle has pores and may be in a brittle state, but by filling the pores with the shell-forming material, the shell can be strengthened without shrinking (for example, softening and shrinking).

[0033] The above-mentioned core particles have a primary particle size of 1≦D SL It is preferable that 1≦D SL ≦1.4, particularly preferably 1≦D SL ≦1.3. The primary particles of the core particles are 1≦D ST It is preferable that 1≦D ST ≦1.4, particularly preferably 1≦D ST ≦1.3. SL and D. ST As mentioned above.

[0034] The aspect ratio of the core particle is preferably less than 2, and more preferably 1.9 or less. On the other hand, the aspect ratio of the core particle is 1 or more, and preferably exceeds 1, and more preferably 1.1 or more. Examples of the shape of the core particle include ellipsoid, sphere, agglomerate, scale, plate, membrane, cylinder, prism, flat, go stone, and rice grain. Preferably, the sphere and go stone shapes are adopted.

[0035] The major axis of the core particle is preferably 0.5 μm or more, more preferably 1 μm or more. On the other hand, the major axis of the core particle is preferably 10 μm or less, more preferably 5 μm or less. On the other hand, the minor axis of the core particle is preferably 0.25 μm or more, more preferably 0.5 μm or more. On the other hand, the minor axis of the core particle is preferably 10 μm or less, more preferably 5 μm or less.

[0036] The core particle forming material is the above-mentioned D SL and D. ST In one embodiment, the core particle is formed of an alunite type compound represented by the following general formula (I). M a [Al 1-x M' x ]3(SO4 2- ) y (OH) z mH2O (I) (In formula (I), M is Na + , K + , NH4 + and H3O + M' is at least one cation selected from the group consisting of Cu 2+ , Zn 2+ , Ni 2+ , Sn 4+ , Zr 4+ and Ti 4+ and a, m, x, y, and z each satisfy 0.8≦a≦1.35, 0≦m≦5, 0≦x≦0.4, 1.7≦y≦2.5, and 4≦z≦7.

[0037] As the shell-forming material, for example, sodium silicate (Na2O·nSiO2) or alkoxysilane such as tetraethoxysilane (Si(OCH2CH3)4) is used. In one embodiment, sodium silicate (water glass) is used. The presence of Na may facilitate softening during firing, which will be described later, and may facilitate control of the firing temperature.

[0038] The amount of coating with the shell-forming material can be adjusted by any suitable method. For example, the amount of coating is adjusted by controlling the pH value when coating is performed using a shell-forming material containing sodium silicate. Specifically, since sodium silicate can be stable in a high pH range (e.g., pH 11 or higher), the sodium silicate molecules are condensed by lowering the pH value, and silica is efficiently precipitated on the core particles. Here, when the core particles contain the above-mentioned alunite type compound, since the aqueous slurry of the alunite type compound itself can be acidic (e.g., pH 3 to 5), for example, silica can be efficiently precipitated on the core particles without using a pH adjuster for lowering the pH value. Note that the formation of the shell (specifically, the precipitation and formation rate of the shell) can also be promoted by heating (e.g., to 80°C to 90°C) when coating with the shell-forming material.

[0039] The amount of coating can also be adjusted by controlling the concentration, amount of the shell-forming material when coating is performed, etc. When the core particles are coated with a shell-forming material containing sodium silicate, the concentration of the shell-forming material (sodium silicate) is, for example, 0.1 mol / L to 2 mol / L.

[0040] The removal of the core particles is typically carried out by dissolving the core particles in an acidic solution. Examples of the acidic solution include hydrochloric acid, sulfuric acid, and nitric acid. The dissolving temperature is, for example, 30°C to 90°C, and preferably 50°C to 80°C. At such a temperature, the core particles can be efficiently dissolved while suppressing problems such as the shell becoming easily broken. In one embodiment, for example, sulfuric acid is used as the acidic solution from the viewpoint of reusing a substance (for example, a salt) obtained by reacting with the core particles. The concentration of sulfuric acid is, for example, 0.1 mol / L to 3 mol / L.

[0041] The method for producing hollow particles may include calcining the core-shell particles before removing the core particles. When the core particles contain the alunite type compound, it is preferable to calcinate the core particles (for example, in an air atmosphere) before removing the core particles. Since the alunite type compound may have acid resistance, the alunite type compound changes by calcination, and the core particles after calcination become easily dissolved in an acidic solution. Specifically, the core particles containing the alunite type compound are easily dissolved in an acidic solution at the portion with a low aggregation density, but are difficult to dissolve in an acidic solution at the portion with a high aggregation density, and the amount of dissolution in an acidic solution is, for example, only about 30% by weight. Calcination produces aluminum oxide (Al2O3), which is easily dissolved in an acidic solution, from the alunite type compound, and the solubility of the core particles in an acidic solution can be improved.

[0042] The firing temperature of the core-shell particles is, for example, 300°C to 900°C, and preferably 300°C to 650°C. Such a firing temperature can suppress crystallization of the shell and generate the aluminum oxide. The firing time is, for example, 0.5 hours to 20 hours. The firing may be performed continuously or in multiple stages at different temperatures. When firing is performed in multiple stages, the firing time is the total of the firing times in each stage.

[0043] The shell-forming material used to coat the hollow particle precursor is preferably selected in accordance with the shell-forming material used to coat the core particle. Specifically, when sodium silicate is used as the shell-forming material used to coat the core particle, sodium silicate is preferably used as the shell-forming material used to coat the hollow particle precursor.

[0044] When the hollow particle precursor is coated with a shell-forming material containing sodium silicate, it is preferable to adjust the coating amount by controlling the pH value. Specifically, since sodium silicate can be stable in a high pH range (e.g., pH 11 or higher), it is preferable to use, for example, a pH adjuster to lower the pH value, thereby condensing sodium silicate molecules and efficiently precipitating silica on the hollow particle precursor. As the pH adjuster, for example, an acidic solution such as hydrochloric acid or sulfuric acid is used.

[0045] The method for producing hollow particles may include calcining the hollow particle precursor coated with a shell-forming material. Specifically, the calcination of the hollow particle precursor may be performed after the hollow particle precursor is coated with the shell-forming material. By calcining the shell, hollow particles that can greatly contribute to improving the dielectric properties can be obtained. Specifically, the hydrophobicity of the shell surface can be improved. More specifically, the silanol groups on the shell surface can be converted to siloxane. In addition, hollow particles that are easy to mix (disperse) in the resin when preparing the resin composition described below can be obtained. Specifically, by causing moderate shrinkage (specifically, softening and shrinkage) by calcination, pores on the shell surface can be filled while preventing fusion between particles, and hollow particles with a smooth surface (for example, the above-mentioned BET specific surface area and pore volume can be well achieved) can be obtained.

[0046] The temperature for firing the hollow particle precursor is, for example, 300°C to 1300°C, preferably 700°C to 1300°C, and more preferably 900°C to 1300°C. Such a firing temperature can satisfactorily achieve the hydrophobicity. In addition, one of the features of the present invention is that a high hollow ratio can be achieved even when firing is performed at such a firing temperature. Specifically, by firing the hollow particle precursor in a state in which the pores are filled with a coating of a shell-forming material, hydrophobicity can be satisfactorily achieved while suppressing the shrinkage of the shell (specifically, softening shrinkage). The firing time for the hollow particle precursor is, for example, 0.1 hours to 10 hours. The firing may be performed continuously or in multiple stages at different temperatures. When firing is performed in multiple stages, the firing time is the total of the firing times of each stage.

[0047] The method for producing hollow particles may include subjecting the hollow particle precursor to an acid treatment before calcining the hollow particle precursor. The acid treatment is typically performed using an acidic solution such as hydrochloric acid or sulfuric acid. When sodium silicate is used as the shell-forming material, the hollow particle precursor may contain Na. By removing Na through the acid treatment, the calcination temperature of the hollow particle precursor can be set high, and hollow particles that can greatly contribute to improving the dielectric properties can be obtained.

[0048] In one embodiment of the present invention, the hollow particles are used as a function-imparting agent for a resin material. A resin composition containing the hollow particles will be described below.

[0049] B. Resin composition The resin composition according to one embodiment of the present invention includes a resin and the hollow particles. In the resin composition (resin molded product described below), the hollow particles can maintain their hollow state well.

[0050] The resin may be any suitable resin selected depending on, for example, the application of the resin composition to be obtained. For example, the resin may be a thermoplastic resin or a thermosetting resin. Specific examples of the resin include epoxy resin, polyimide resin, polyamide resin, polyamideimide resin, polyetheretherketone resin, polyester resin, polyhydroxypolyether resin, polyolefin resin, fluororesin, liquid crystal polymer, and modified polyimide. These may be used alone or in combination of two or more.

[0051] The content of the hollow particles in the resin composition is preferably 0.1% by weight or more, more preferably 0.5% by weight or more, while the content is preferably 90% by weight or less, more preferably 85% by weight or less.

[0052] The resin composition preferably contains 0.5 parts by weight or more of hollow particles per 100 parts by weight of resin, more preferably 1 part by weight or more, while the resin composition preferably contains 300 parts by weight or less of hollow particles per 100 parts by weight of resin, more preferably 200 parts by weight or less.

[0053] The volume ratio of hollow particles in the resin composition is preferably 0.1% or more, more preferably 0.5% or more. On the other hand, the volume ratio of hollow particles in the resin composition is preferably 70% or less, more preferably 60% or less. For example, this is because the processability during preparation of the resin composition can be excellent.

[0054] The hollow ratio of the particles (filler) in the resin composition (resin molded product) is preferably 30% or more, more preferably 40% or more, further preferably 45% or more, and particularly preferably 50% or more.

[0055] The resin composition may contain an optional component. Examples of the optional component include a curing agent (specifically, a curing agent for the resin), a stress reducing agent, a coloring agent, an adhesion improver, a release agent, a flow control agent, a defoaming agent, a solvent, and a filler. These may be used alone or in combination of two or more. In one embodiment, the resin composition contains a curing agent. The content of the curing agent is, for example, 1 part by weight to 150 parts by weight relative to 100 parts by weight of the resin.

[0056] Any suitable method can be adopted as the method for preparing the resin composition. Specifically, the hollow particles are dispersed in the resin by any suitable dispersion method to obtain the resin composition. Examples of the dispersion method include dispersion by various agitators such as homomixer, disperser, and ball mill, dispersion by a planetary mixer, dispersion by shear force using a three-roll mill, and dispersion by ultrasonic treatment.

[0057] The resin composition is typically formed into a resin molded product having a desired shape. For example, the resin composition is formed into a resin molded product having a desired shape using a mold. When forming the resin molded product, the resin composition may be subjected to any appropriate treatment (for example, a curing treatment).

[0058] In one embodiment of the present invention, the resin composition is a resin layer included in a laminate. A laminate having a resin layer formed from the resin composition will be described below.

[0059] C. Laminate 2 is a schematic cross-sectional view of a laminate in one embodiment of the present invention. The laminate 10 has a resin layer 11 and a metal foil 12. The resin layer 11 is formed from the resin composition. Specifically, the resin layer 11 contains the resin and the hollow particles. Although not shown, the laminate 10 may contain other layers. For example, a substrate (typically, a resin film) laminated on one side of the resin layer 11 (the side on which the metal foil 12 is not disposed) can be mentioned. The laminate 10 is typically used as a wiring circuit board.

[0060] The thickness of the resin layer is, for example, 5 μm or more, preferably 10 μm or more. On the other hand, the thickness of the resin layer is, for example, 100 μm or less, preferably 50 μm or less, and more preferably 25 μm or less. With such a thickness, for example, it is possible to fully respond to the miniaturization of electronic components in recent years.

[0061] Any suitable metal can be used as the metal for forming the metal foil. Examples include copper, aluminum, nickel, chromium, and gold. These can be used alone or in combination of two or more. The thickness of the metal foil is, for example, 2 μm to 35 μm.

[0062] Any suitable method may be adopted as a method for producing the laminate. For example, the resin composition is applied to the substrate to form a coating layer, and the metal foil is laminated on the coating layer to obtain a laminate. As another specific example, the resin composition is applied to the metal foil to form a coating layer to obtain a laminate. Typically, the coating layer is cured by subjecting the coating layer to a treatment such as heating or light irradiation at any suitable timing. When coating, the resin composition may be dissolved in any suitable solvent and used. EXAMPLES

[0063] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. The methods for measuring each property are as follows, unless otherwise specified. 1. Major axis of particle The long diameter of the particles was calculated by FE-SEM observation. Specifically, the long diameter of 100 primary particles randomly selected from the SEM photograph of the particles was measured, and the arithmetic mean (average long diameter) of the obtained measurements was calculated. The magnification of the SEM observation was 10,000 times. 2. Minor diameter of particle The minor axis of the particles was calculated by FE-SEM observation. Specifically, the minor axis of 100 primary particles randomly selected from the SEM photographs of the particles was measured, and the arithmetic mean of the obtained measurements (average minor axis) was calculated. The magnification of the SEM observation was 10,000 times. 3.D SL and D.ST The calculation was performed by FE-SEM observation. Specifically, the major axis of each of 100 primary particles randomly selected from the SEM photograph of the particles was measured, and the 75th value (D 75L ) to the 25th value (D 25L ) and divide by D SL In addition, the short diameter of each of 100 primary particles randomly selected from the SEM photograph of the particles was measured, and the 75th value (D 75T ) to the 25th value (D 25T ) and divide by D ST was calculated. 4. Aspect Ratio The aspect ratio was calculated by FE-SEM observation. Specifically, the aspect ratio was calculated by dividing the average major axis of the particles by the average minor axis of the particles. 5. Shell thickness of hollow particles The shell thickness of the particles was calculated by TEM observation. Specifically, the shell thickness of 10 primary particles randomly selected from the TEM photographs of the particles was measured, and the arithmetic mean (average thickness) of the obtained measurements was calculated. The magnifications of the TEM observation were 10,000x and 100,000x. 6.Hollow rate The hollow ratio was calculated from the major axis and minor axis and the thickness of the shell. Specifically, the primary particle diameter (major axis, minor axis) and the thickness of the shell were used to approximate the particle shape with the volume of a cylinder, and the hollow ratio was calculated by the following formula. Hollow ratio = hollow volume of hollow particle ÷ volume of hollow particle × 100 Volume of a hollow particle = π x radius 2 × height = π × (major axis ÷ 2) 2 × Short diameter Hollow volume of hollow particle = π × ((long diameter - shell thickness × 2) ÷ 2) 2 ×(minor axis - shell thickness × 2) 7.BET specific surface area Measurements were performed using a "BELsorp-mini" made by Microtrack-Bell Co., Ltd. Specifically, measurements were performed using a constant volume gas adsorption method using nitrogen gas, and the specific surface area was calculated by analysis using the BET multipoint method. 8. Pore volume Measurements were performed using a "BELsorp-max" from Microtrack-Bell Co., Ltd. Specifically, measurements were performed using a constant volume gas adsorption method using nitrogen gas, and the pore volumes (cumulative pore volumes of pores with diameters of 1 nm to 100 nm and cumulative pore volumes of pores with diameters of 1 nm to 10 nm) were calculated using analysis by the BJH method. 9.Breaking strength The breaking strength was measured using a micro-compression tester (Shimadzu Corporation's "MCT-510") with a length measurement kit and a side observation kit. Specifically, a very small amount of the sample was scattered on the lower pressure plate, and a breaking test was performed on each particle under the following conditions. Test force: 0.980mN ·Load speed: 0.0223mN / sec ·Top pressure indenter: flat surface φ20μm Measurements were made on 10 particles, and the breaking strength Cs (MPa) was calculated from the particle diameter d (mm) of the measured particles and the test force P (N) at the breaking point, and the average value was calculated. The breaking strength Cs was calculated from the following formula in JIS R 1639-5 "Measurement method for fine ceramic granule characteristics - Part 5: Single granule crushing strength". Cs=2.48P / πd 2 10.KM converted silanol group area The amount of silanol groups (silanol group area) was measured by FT-IR diffuse reflectance spectroscopy. Specifically, the measurement was performed using a diffuse reflectance measurement kit (JASCO Corporation's "DR PRO410-M type") on a Fourier transform infrared spectrophotometer (JASCO Corporation's "FT / IR-4100"), with 0.017 g of KBr as background sample and a given amount (0.0014 g to 0.0031 g) of measurement sample. The obtained spectrum was subjected to KM (Kubelka-Munk) conversion processing and quantitative analysis was performed. -1 ~3100cm -1 The peak area was determined, and the KM converted silanol group area per unit weight (- / g) was calculated. In addition, the range is 3900 cm -1 ~3100cm -1 3740cm -1Isolated silanol group, 3650cm -1 adjacent isolated silanol groups, 3400cm -1 This includes silanol groups derived from nearby surface-adsorbed water.

[0064] [Example 1] (Preparation of Hollow Silica Particles) Elliptical alunite particle powder (NaAl3(SO4)2(OH)6, major axis: 1.98 μm, D SL :1.13, Short diameter: 1.35μm, D ST A 100 g sample of the sintered material (size: 1.18, aspect ratio: 1.47) was suspended in 0.675 L of ion-exchanged water to obtain a slurry of alunite particles.

[0065] The resulting slurry of alunite particles was then heated to 90°C while stirring, and 98.62 ml of 0.538 mol / L No. 3 water glass (Na2O 3.14SiO2, Fujifilm Wako Pure Chemical Industries, Ltd.) was added thereto over a period of 4 hours. The slurry thus obtained was aged for 1 hour, then dehydrated and washed with water to obtain a cake of core-shell particle precursor 1.

[0066] Next, the obtained cake of core-shell particle precursor 1 was suspended in 0.675 L of ion-exchanged water, heated to 90°C while stirring, and 98.62 ml of 0.538 mol / L No. 3 water glass was added thereto over 2 hours. The slurry thus obtained was aged for 1 hour, left for 15 hours while stirring, then dehydrated and washed with water to obtain a cake of core-shell particle precursor 2. The obtained cake of core-shell particle precursor 2 was suspended in 0.675 L of ion-exchanged water, heated to 90°C while stirring, and 98.62 ml of 0.538 mol / L No. 3 water glass was added thereto over 2 hours. The slurry thus obtained was aged for 1 hour, left for 15 hours while stirring, then dehydrated and washed with water, and then dried at 100°C for 1 day to obtain a powder of core-shell particles.

[0067] The obtained powder of core-shell particles was then fired at 500° C. for 3 hours and then at 550° C. for 1 hour. It is believed that the firing caused the alunite particles to change as follows. NaAl3(SO4)2(OH)6→NaAl(SO4)2+Al2O3+3H2O

[0068] Next, 1 L of ion-exchanged water was added to 101.4 g of the calcined core-shell particles, and the particles were resuspended under stirring at room temperature, to which 866 ml of 1.1 mol / L sulfuric acid was added, heated to 90°C, and reacted for 5 hours to dissolve the core particles, yielding a slurry of hollow silica precursor 1. The resulting slurry of hollow silica precursor 1 was dehydrated and washed with water to obtain a cake of hollow silica precursor 1.

[0069] Next, the obtained cake of hollow silica precursor 1 was suspended in 1L of ion-exchanged water and heated to 90°C while stirring. 7.4ml of 0.538mol / L No. 3 water glass was added over 10 minutes, and then 36.98ml of 0.538mol / L No. 3 water glass and 42.99ml of 0.5mol / L sulfuric acid were added simultaneously. No. 3 water glass was added over 50 minutes, and sulfuric acid was added over 60 minutes. The slurry thus obtained was aged for 30 minutes, and then dehydrated and washed with water to obtain a cake of hollow silica precursor. The same operation was repeated two more times to obtain a cake of hollow silica precursor 2.

[0070] Next, 0.675 L of ion-exchanged water and 46 ml of 2 mol / L sulfuric acid were added to the obtained cake of hollow silica precursor 2, and the mixture was left at 90°C for 1.5 hours to obtain a slurry of hollow silica precursor 3. The cake obtained after dehydration and washing with water was then dried at 100°C for 1 day to obtain a powder of hollow silica precursor 3.

[0071] Next, the obtained powder of hollow silica precursor 3 was baked in an electric furnace (in an air atmosphere) at 1100° C. for 2 hours to obtain hollow silica particles (major axis: 1.96 μm, D SL :1.13, minor axis: 1.63μm, D ST : 1.33, aspect ratio: 1.20, shell thickness: 97 nm, hollow ratio: 72%, BET specific surface area: 7.5 m 2The results are shown in Table 1. The hollow silica particles obtained had a molecular weight of 0.018, a pore volume of 0.033cc / g, a fracture strength of 20.8MPa, and a KM converted silanol group area of ​​695- / g. The ratio of Al derived from the core particles to Si derived from the silica shell was calculated by composition analysis of the obtained hollow silica particles using EDS measurement with a JEOL Ltd. "JED-2300," and the molar ratio of Al / Si was found to be 0.018.

[0072] (Preparation of Resin Composition) 44.23 g of bisphenol F type epoxy resin ("JER806" manufactured by Mitsubishi Chemical Corporation) and 9.00 g of the obtained hollow silica particles (also called filler) were mixed for 3 minutes under atmospheric pressure at 1000 rpm rotation and 2000 rpm revolution using a planetary centrifugal mixer ("ARV-310P" manufactured by Thinky Corporation) to obtain a mixture. The resulting mixture and 2.21 g of an imidazole-based epoxy resin curing agent ("2E4MZ" manufactured by Shikoku Kasei Co., Ltd.) were mixed for 3 minutes using a planetary centrifugal mixer under conditions of a rotation of 1000 rpm, a revolution of 2000 rpm, and 0.7 kPa to obtain a resin composition.

[0073] (Preparation of resin molded body) The obtained resin composition was poured into a 1.0 mm thick Teflon mold and press molded at 80° C. for 1 hour. After cooling, the molded product was removed from the mold and placed in a dryer at 150° C. for 4 hours for further heat curing. The molded product was then cooled to obtain an evaluation sample.

[0074] [Example 2] (Preparation of Hollow Silica Particles) Elliptical alunite particle powder (NaAl3(SO4)2(OH)6, major axis: 1.98 μm, D SL :1.13, Short diameter: 1.35μm, D ST A 100 g sample of the sintered material (size: 1.18, aspect ratio: 1.47) was suspended in 0.5 L of ion-exchanged water to obtain a slurry of alunite particles.

[0075] The resulting slurry of alunite particles was then heated to 90°C while stirring, and 100 ml of 0.528 mol / L No. 3 water glass (Na2O 3.14SiO2, Fujifilm Wako Pure Chemical Industries, Ltd.) was added thereto over a period of 4 hours. The slurry thus obtained was aged for 1 hour, after which it was dehydrated and washed with water to obtain a cake of core-shell particle precursor 1.

[0076] Next, the obtained cake of core-shell particle precursor 1 was suspended in 0.5 L of ion-exchanged water, heated to 90°C while stirring, and 150 ml of 0.538 mol / L No. 3 water glass was added thereto over 2 hours. The slurry thus obtained was aged for 1 hour, left for 15 hours while stirring, then dehydrated and washed with water to obtain a cake of core-shell particle precursor 2. The obtained cake of core-shell particle precursor 2 was suspended in 0.5 L of ion-exchanged water, heated to 90°C while stirring, and 150 ml of 0.538 mol / L No. 3 water glass was added thereto over 2 hours. The slurry thus obtained was aged for 1 hour, left for 15 hours while stirring, then dehydrated and washed with water, and then dried at 100°C for 1 day to obtain a powder of core-shell particles.

[0077] The obtained powder of core-shell particles was then fired at 500° C. for 3 hours and then at 550° C. for 1 hour. It is believed that the firing caused the alunite particles to change as follows. NaAl3(SO4)2(OH)6→NaAl(SO4)2+Al2O3+3H2O

[0078] Next, 1 L of ion-exchanged water was added to 90.7 g of the calcined core-shell particles, and the particles were resuspended under stirring at room temperature, to which 688 ml of 1.1 mol / L sulfuric acid was added, and the mixture was heated to 90°C and reacted for 5 hours to dissolve the core particles, yielding a slurry of hollow silica precursor 1. The obtained slurry of hollow silica precursor 1 was dehydrated and washed with water to obtain a cake of hollow silica precursor 1.

[0079] Next, the obtained cake of hollow silica precursor 1 was suspended in 1L of ion-exchanged water and heated to 90°C while stirring. 26.18ml of 0.538mol / L No. 3 water glass was added over 10 minutes, and then 130.82ml of 0.538mol / L No. 3 water glass and 149.88ml of 0.5mol / L sulfuric acid were added simultaneously. No. 3 water glass was added over 50 minutes, and sulfuric acid was added over 60 minutes. The slurry thus obtained was aged for 30 minutes, and then dehydrated and washed to obtain a cake of hollow silica precursor. The same operation was repeated two more times, and the obtained cake was dried at 100°C for one day to obtain a powder of hollow silica precursor 2.

[0080] Next, the obtained powder of hollow silica precursor 2 was baked in an electric furnace (in an air atmosphere) at 1100° C. for 2 hours to obtain hollow silica particles (long diameter: 2.16 μm, D SL :1.10, Short diameter: 1.85μm, D ST : 1.15, aspect ratio: 1.17, shell thickness: 235 nm, hollow ratio: 46%, BET specific surface area: 4.8 m 2 / g, pore volume: 0.029cc / g, KM converted silanol group area: 663- / g). The molar ratio of Al / Si was 0.019.

[0081] (Preparation of resin molded body) A molded product (evaluation sample) was obtained in the same manner as in Example 1, except that the above hollow silica particles were used and the amount of hollow silica particles was 13.93 g.

[0082] [Comparative Example 1] (Preparation of Hollow Silica Particles) Elliptical alunite particle powder (NaAl3(SO4)2(OH)6, major axis: 1.48 μm, D SL :1.10, Short diameter: 1.08μm, D ST A 2.38 kg sample (aspect ratio: 1.09, aspect ratio: 1.36) was suspended in 15.8 L of ion-exchanged water to obtain a slurry of alunite particles.

[0083] The resulting slurry of alunite particles was then heated to 90°C while stirring, and 2.322 L of 0.57 mol / L No. 3 water glass (Na2O 3.14SiO2, Fujifilm Wako Pure Chemical Industries, Ltd.) was added thereto over a period of 4 hours. The slurry thus obtained was aged for 1 hour, then dehydrated and washed with water to obtain a cake of core-shell particle precursor 1.

[0084] Next, the obtained cake of core-shell particle precursor 1 was suspended in 15.8 L of ion-exchanged water, heated to 90°C while stirring, and 2.322 L of 0.57 mol / L No. 3 water glass was added thereto over 2 hours. The slurry thus obtained was aged for 1 hour, then dehydrated and washed with water to obtain a cake of core-shell particle precursor 2. The obtained cake of core-shell particle precursor 2 was suspended in 15.8 L of ion-exchanged water, heated to 90°C while stirring, and 2.322 L of 0.57 mol / L No. 3 water glass was added thereto over 2 hours. The slurry thus obtained was aged for 1 hour, then dehydrated and washed with water, and then dried at 100°C for 1 day to obtain a powder of core-shell particles.

[0085] The obtained powder of core-shell particles was then fired at 500° C. for 3 hours and then at 550° C. for 1 hour. It is believed that the firing caused the alunite particles to change as follows. NaAl3(SO4)2(OH)6→NaAl(SO4)2+Al2O3+3H2O

[0086] Next, 1 L of ion-exchanged water was added to 2170 g of the calcined core-shell particles, and the particles were resuspended under stirring at room temperature. 15 L of 1.26 mol / L sulfuric acid was added to this, and the mixture was heated to 90°C and reacted for 5 hours to dissolve the core particles, yielding a slurry of hollow silica precursor 1. The resulting slurry of hollow silica precursor 1 was dehydrated and washed with water to obtain a cake of hollow silica precursor 1. The resulting cake was dried at 100°C for 1 day to obtain a powder of hollow silica precursor 1.

[0087] The obtained powder of hollow silica precursor 1 was then calcined in an electric furnace (in an air atmosphere) at 800° C. for 2 hours to obtain hollow silica particles (long diameter: 1.55 μm, D SL: 1.10, minor axis: 1.12 μm, D ST : 1.14, aspect ratio: 1.38, shell thickness: 54 nm, hollowness: 78%, BET specific surface area: 39 m 2 / g, pore volume: 0.136 cc / g, KM conversion silanol group area: 230718 - / g) was obtained. The molar ratio of Al / Si was 0.027.

[0088] (Preparation of resin molded body) A molded body (sample for evaluation) was obtained in the same manner as in Example 1 except that the above hollow silica particles were used and the blending amount of the hollow silica particles was 2.79 g. Although an attempt was made to blend the hollow silica particles in an amount equivalent to that in the examples, the particles were broken, or thickening and heat generation due to frictional heat occurred in the varnish in which the particles were blended with the epoxy resin and the curing agent, promoting the curing of the resin, and further blending was not possible. As a reason for not being able to achieve an amount equivalent to that in the examples, an increase in specific surface area due to high BET specific surface area, high pore volume, high amount of silanol groups, and breakage of hollow particles is considered.

[0089] [Comparative Example 2] A molded body (sample for evaluation) was obtained in the same manner as in Example 1 except that no hollow silica particles were blended.

[0090] [XRD measurement] When the hollow silica particles of Example 1, 2 and Comparative Example 1 were analyzed by X-ray diffraction (''EMPYRIAN'' manufactured by PANalytical), they were amorphous silica.

[0091] [FE-SEM observation] The hollow silica particles of Example 1, 2 and Comparative Example 1 were observed with a scanning electron microscope (''JSM-7600F'' manufactured by JEOL Ltd.) (magnification: 10,000 times). The observation results of the hollow silica particles of Example 1 are shown in Fig. 3A, the observation results of the hollow silica particles of Example 2 are shown in Fig. 3B, and the observation results of the hollow silica particles of Comparative Example 1 are shown in Fig. 3C. In each case, it was confirmed that the particles had a uniform particle size.

[0092] <TEM Observation> For the hollow silica particles of Example 1, Example 2, and Comparative Example 1, observation was carried out using a transmission electron microscope (“JEM - 2100PLUS” manufactured by JEOL Ltd.) (Magnification: 10,000 times). The observation results of the hollow silica particles of Example 1 are shown in Fig. 4A, the observation results of the hollow silica particles of Example 2 are shown in Fig. 4B, and the observation results of the hollow silica particles of Comparative Example 1 are shown in Fig. 4C. In each case, it was confirmed that the particles are hollow particles maintaining the elliptical shape of the core particles.

[0093] <Evaluation of Resin Moldings> For the resin moldings (evaluation samples) of the examples and comparative examples, density, cross - sectional observation, and measurement of dielectric properties were carried out. Also, the porosity of the resin molding and the filler hollow ratio in the resin molding were calculated. The evaluation results are summarized in Table 1. Also, the observation results of the resin molding of Example 1 are shown in Fig. 5A, the observation results of the resin molding of Example 2 are shown in Fig. 5B, and the observation results of the resin molding of Comparative Example 1 are shown in Fig. 5C.

[0094] (Measurement of Density) The density of the resin molding was measured using an electron density meter (“SD120L” manufactured by Alpha Mirage Co., Ltd.). Specifically, the obtained resin molding was cut into a size of 5 cm × 6 cm with an ultrasonic cutter, and the molded body sample obtained by cutting was used for measurement.

[0095] (Porosity of Resin Molding) From the measurement results of the above density, the porosity Va% (the ratio of the volume of air in the resin molding) of the resin molding was calculated. (Filler Hollow Ratio in Resin Molding) From the value of the porosity Va% of the above resin molding, the filler hollow ratio Va / (Va + Vs) in the resin molding was calculated. Here, Vs can be obtained from the following formula.

Equation

[0096] (Cross-section observation of resin molded body) The obtained molded body sample was cut using a cross-section polisher ("IB-09010CP" manufactured by JEOL Ltd.), and the cross section was observed using a FE-SEM ("JSM-7600F" manufactured by JEOL Ltd., magnification: 5000x or 10000x).

[0097] (Measurement of dielectric constant and dielectric loss tangent) The dielectric constant and dielectric loss tangent of the obtained molded sample were measured under the following conditions. Measurement method: Compliant with IEC 62810 (cavity resonator perturbation method) -Sample shape: Length 55mm or more, width 1.6~2.4mm, height 0.7~1.0mm Test conditions: Frequency 10GHz Number of measurements: 2 Conditioning: 23℃±1℃, 50%RH±5%RH, 24 hours Test room environment: 23℃±1℃, 50%RH±5%RH Measurement equipment: PNA network analyzer N5222B (Keysight Technologies, Inc.) Cavity resonator: CP531 for 10GHz (manufactured by Kanto Electronics Application Development Co., Ltd.)

[0098] [Table 1]

[0099] In Comparative Example 1, it can be seen that the hollow ratio is greatly reduced by blending with the resin. In Comparative Example 1, destruction of hollow particles was confirmed by cross-sectional observation of the resin molded product, and infiltration of resin into the hollow region was also confirmed as shown in Fig. 5C. On the other hand, in the Examples, infiltration of resin into the hollow region was not confirmed by cross-sectional observation of the resin molded product, and it was confirmed that destruction of hollow particles was suppressed (particularly in Example 2). The reason why the dielectric loss tangent was not reduced in Comparative Example 1 is thought to be that the amount of silanol groups was large. [Industrial Applicability]

[0100] The hollow particles of the present invention can be suitably used, typically, in electronic materials, and can also be used, for example, in heat insulating materials, soundproofing materials, shock absorbing materials, stress absorbing materials, optical materials, and lightweight materials. [Explanation of symbols]

[0101] L Major axis T Short diameter 10 Laminate 11 Resin layer 12 Metal foil

Claims

1. Contains silica, primary particles of D SL Hollow particles satisfying the following formula (1), having a breaking strength of 10 MPa or more, containing Al, and having an Al / Si molar ratio of 0.0001 or more and 0.08 or less: 1≦D SL ≦1.5・・・(1) Here, D SL =D 75L / D 25L And D 25L and D. 75L In observation by a scanning electron microscope, the major axis of 100 randomly selected primary particles is measured, and the 25th and 75th largest values ​​are indicated when the particles are arranged in order of size from smallest to largest.

2. BET specific surface area is 30m 2 The hollow particle according to claim 1 , wherein the molecular weight is 1 / g or less.

3. 3. The hollow particle according to claim 1, wherein an integrated pore volume of pores having a diameter of 1 nm to 100 nm is 0.1 cc / g or less.

4. 4. The hollow particle according to claim 1, wherein the hollow ratio is 30% or more and 95% or less.

5. 5. The hollow particle according to claim 1, having an aspect ratio of less than 2.

6. 6. The hollow particle according to claim 1, wherein the major axis is from 0.5 μm to 10 μm.

7. 7. The hollow particle according to claim 1, wherein the shell has a thickness of 25 nm or more and 500 nm or less.

8. 8. The hollow particle according to claim 1, wherein the silica is amorphous silica.

9. 9. The hollow particle according to claim 1, which contains Na and has a molar ratio of Na / Si of 0.001 or more and 0.025 or less.

Citation Information

Patent Citations

  • Preparation method of SiO2 / ZrO2 / Al2O3 composite hollow nanospheres

    CN103570027A

  • Particles uniform in particle diameter and production thereof

    JP1995265686A

  • Silica-based microparticle, method for producing dispersion with the same, and base material with coating film

    JP2001233611A

  • Transparent film-applied base material, coating solution for forming transparent film and display device

    JP2002079616A

  • Method of manufacturing optical film and antireflection film, optical film, antireflection film, polarizing plate, and image display device using them

    JP2006099081A